STRATEGI PEMERINTAH DESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA MELALUI BADAN USAHA MILIK DESA - Nur Cisan Imran Kurman; Dody Setyawan; Noora Fithriana (Universitas Tribhuwana Tungga Dewi, 2021)
BUMDes is an institution established by the Village Government which has an important role in increasing Village Original Income. Therefore, the Village Government must pay special attention to developing these BUMDes efforts by making a strategy that is seen from the formulation and long-term targets, selection of actions, and allocation of resources. This study aimed to determine the strategy of the Oro Oro Ombo Village Government of Batu City in increasing PADesa through Panderman BUMDes. This study used the descriptive qualitative method. The data collection used by the researcher in this research is interviews, observation, and documentation. The technique of determining informants is using Snowball Sampling. Data analysis used data reduction, data display, and conclusion/verification. The results of this study, in increasing PADesa, among others, the Village Government provides strategies in the form of coaching and training, providing capital participation, and facilitating managed business units. With this strategy, the management of Panderman BUMDes business units runs smoothly. It can be seen from the increase in Panderman BUMDes income allocated to PADesa in 2018 of IDR. 16,800,000, and increased in 2019 by IDR. 21,600,000. Supporting factors in increasing PADesa are the formulation and long-term goals, selection of actions, and the allocation of natural resources and financial resources. The inhibiting factor in increasing PADesa through Panderman BUMDes is the lack of awareness of human resources in managing Panderman BUMDes, which causes some business units not to operate optimally. Because of this problem, the village government will restructure the BUMDesPanderman so that the resources for managing the BUMDes Panderman are more developed.Keywords: Original Income, Village Business Entity, StrategyBUMDes sebagai lembaga yang didirikan oleh pemerintah desa mempunyai peranan untuk meningkatkan PADesa. Untuk itu, pemerintah desa perlu melakukan tindakan untuk kemajuan usaha BUMDes dan mewujudkan strategi dari sisi formulasi dan sasaran jangka panjang, pemilihan tindakan dan alokasi sumberdaya. Tujuan dari penelitian ini adalah untuk melihat strategi Pemerintah Desa Oro-Oro Ombo dalam meningkatkan PADesa melalui BUMDes Panderman. Penelitian ini menggunakan metode kualitatif. Data primer diperoleh melalui wawancara, observasi dan dokumentasi sedangkan data sekunder dari dokumen-dokumen. Informan ditunjuk dengan snowball sampling. Analisis data menggunakan tahapan-tahapan mulai dari data reduction, data display hingga conclusion/verification. Dari hasil penelitian ini diketahui bahwa Pemerintah Desa Oro-Oro Ombo melakukan strategi berupa pembinaan, pelatihan, penyertaan modal, serta fasilitasi unit usaha BUMDes Panderman. Strategi-strategi ini dapat meningkatkan PADesa dimana pendapatan BUMDes Panderman yang dialokasikan ke PADesa Tahun 2018 sejumlah Rp. 16.800.000,-. Dengan jumlah ini didapati kenaikan PADesa Tahun 2019 sejumlah Rp. 21.600.000,-. Faktor pendukung dalam peningkatan PADesa adalah formulasi dan sasaran jangka panjang, pemilihan tindakan dan alokasi sumberdaya alam dan sumberdaya keuangan. Adapun faktor penghambatnya adalah belum adanya kesadaran sumberdaya manusia dalam mengelola BUMDes Panderman sehingga menyebabkan sebagian unit usaha tidak beroperasional secara maksimal. Oleh sebab itu, Pemerintah Desa Oro-Oro Ombo melakukan restrukturisasi BUMDes Panderman agar lebih berkembang.Kata Kunci: Pendapatan Asli, Badan Usaha Desa, Strategi